2015
DOI: 10.1002/elps.201500033
|View full text |Cite
|
Sign up to set email alerts
|

Metalless electrodes for capacitively coupled contactless conductivity detection on electrophoresis microchips

Abstract: This paper describes the use of ionic solutions as sensing electrodes for capacitively coupled contactless conductivity detection on electrophoresis microchips. Initially, two channels were engraved in a PMMA holder by using a CO2 laser system and sealed with a thin adhesive membrane. PDMS electrophoresis chips were fabricated by soft lithography and reversibly sealed against the polymer membrane. Different ionic solutions were investigated as metalless electrodes. The electrode channels were filled with KCl s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In the proposed approach, we have made use of just paper and pencil to produce sensing electrodes for C 4 D. When compared to metal (Au, Pt, Cu, Al, etc.) electrodes fabricated by sputtering , polymeric electrodes prepared by laser cutting or even low cost electrodes produced with metal adhesive tapes , aluminum foil , printed circuit boards , alloys , and electrolytic solutions , the production of PDE is simpler, faster, and cheaper. Furthermore, the proposed electrodes for C 4 D can be drawn in different geometries.…”
Section: Resultsmentioning
confidence: 99%
“…In the proposed approach, we have made use of just paper and pencil to produce sensing electrodes for C 4 D. When compared to metal (Au, Pt, Cu, Al, etc.) electrodes fabricated by sputtering , polymeric electrodes prepared by laser cutting or even low cost electrodes produced with metal adhesive tapes , aluminum foil , printed circuit boards , alloys , and electrolytic solutions , the production of PDE is simpler, faster, and cheaper. Furthermore, the proposed electrodes for C 4 D can be drawn in different geometries.…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain better separation resolution the detection gap of C 4 D should be shortened. The detection gap of the applied C 4 D was 500 μm (the usual gap sizes are ranged from 500 μm to 2 mm, ). For the ∼100 μm length plug of sample (typical for chip electrophoresis, where the effective length is 6–10 cm), the optimal detection gap could be around 20–100 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a large number of lab‐made microchips are manufactured from PDMS because this material is a flexible, inexpensive, optically transparent polymer for optical detection, offering a relative ease of fabrication of a complex microfluidic system without sophisticated instrumentation . However, only a few papers could be found about the use of a PDMS chip with C 4 D detection. Guijt reported a reusable, reversibly bonded PDMS‐hybrid device using a dry photoresist insulating layer with the electrodes prepared by printed circuit board technology .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous microchip designs, metallic C 4 D electrodes were usually embedded into the microchannel structure and were covered by a thin layer of insulating material for good transmission of the ac signal from the function generator into the separation channel and from the separation channel into the current‐to‐voltage processing circuitry. Coltro and coworkers demonstrated that the material for C 4 D electrodes can be formed by conductive solutions embedded directly underneath the separation microchannel. Two electrode channels (1 × 1 mm) were engraved in a PMMA substrate, sealed with a thin adhesive membrane (40 μm) and bonded with a lithographically fabricated PDMS microchip.…”
Section: Fundamental Characterization and Modified Detector Designsmentioning
confidence: 99%